2013
DOI: 10.1177/0004865813483296
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and government: Between history and criminology

Abstract: Incontestably the decade since 9/11 has been the pre-eminent age of terrorism. Or has it? In this lecture we consider terrorism as an object of government and of academic research. In arguing that law and criminology have been the pre-eminent disciplines attending to governmental responses to terrorism we note that their interventions have been significant in both their critical stance and in their impact in shaping discourse about the tactics and limits of counter-terrorism, particularly legislation and its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The first 15 years of the twenty-first century have undoubtedly been marked by the impact of international terrorism (Finnane 2013). That which Roach (2011) has called the '9/11 effect' has tentacles that have reached out into the far corners of the world (Howie 2012).…”
Section: Thinking About Violent Extremismmentioning
confidence: 99%
“…The first 15 years of the twenty-first century have undoubtedly been marked by the impact of international terrorism (Finnane 2013). That which Roach (2011) has called the '9/11 effect' has tentacles that have reached out into the far corners of the world (Howie 2012).…”
Section: Thinking About Violent Extremismmentioning
confidence: 99%
“…Our approach builds upon a body of criminological and drug policy literature, which has examined the history of crime policies in Australia including counter-terrorism responses (Finnane, 2013;Hogg, 2007), state responses to Aboriginal violence (Finnane & Richards, 2010), and rape legislation (Brereton, 1994), as well as the historical development of drug policies including drug trafficking thresholds (Hughes, Ritter, & Cowdery, 2014) and drug diversion (Hughes, 2009). By taking an historical view, each of these studies has revealed the complexities of crime policy development, thus challenging assumptions that counter-terrorism responses are 'new' or that drug trafficking thresholds were 'evidence-informed', for example.…”
Section: Introductionmentioning
confidence: 99%